ANALISA KEKUATAN MEMANJANG KAPAL PONTON LOA 100,5 METER - Widyo Nugroho Ridlo; Dimas Endro Witjonarko Raden; Gafur Abdul (Politeknik Perkapalan Negeri Surabaya, 2018)
Pontoon is ships which is carrying material on their deck. Usually it is not self-propelled vessel. So it must be towed by tug boat. One of important things in ship’s transportation is an analysis of its longitudinal strength. It is very important because we have to make sure the ships will be safe when sailing. In this analysis, we have calculate maximum moment that occurs in the ships while the ships is in hogging and sagging condition. There are two method to analize this case, they are calculation and simulation in Maxsurf software. And the result is the maximum moment that occurs is 19.729,14 ton.m from calculation in hogging condition and -26,398 ton.m from simulation in sagging condition.